Meropenem pharmacokinetics during extracorporeal membrane oxygenation and continuous haemodialysis: a case report. (September 2020) - Saito, Jumpei; Shoji, Kensuke; Oho, Yusuke; Aoki, Satoshi; Matsumoto, Shotaro; Yoshida, Michiko; Nakamura, Hidefumi; Kaneko, Yukihiro; Hayashi, Taiyu; Yamatani, Akimasa; Capparelli, Edmund; Miyairi, Isao
Highlights: For an infant case on ECMO and continuous haemodialysis, high-dose meropenem was required. Prolonged high-dose infusion may be needed to achieve desirable target meropenem exposure. Individualised meropenem dosing is needed for infants on ECMO and continuous haemodialysis. Abstract: Objectives: Pharmacokinetic (PK) parameters can change significantly during extracorporeal membrane oxygenation (ECMO) and continuous haemodialysis. This case report describes the pharmacokinetics of a 3-h meropenem infusion in an infantile anuric patient on ECMO with continuous haemodialysis. Case: A 19-month-old female patient with asplenia syndrome was admitted to the paediatric intensive care unit for postoperative management of an extracardiac total cavopulmonary connection procedure. Veno-arterial ECMO and continuous haemodialysis were initiated on postoperative Day 2 for circulatory insufficiency due to septic shock and thrombosis of the inferior vena cava extending to the pulmonary artery. Blood and ascites cultures were positive for extended-spectrum β-lactamase-producing Escherichia coli, and 3-h meropenem infusions [120–300 mg/kg/day divided every 8 h (q8h)] were commenced. Following dose escalation to 300 mg/kg/day q8h, sustained negative blood cultures were confirmed. The estimated meropenem clearance and volume of distribution ( V d ) were 2.21 mL/kg/min and 0.59 L/kg, respectively. These patient-specific PK parameters were used to predict the PK profile of various dosing regimens. Both 1-h and 3-h infusions of meropenem at 60, 120 and 200 mg/kg/day q8h predicted that the free drug concentration would remain above the minimum inhibitory concentration ( f T>MIC ) at an MIC of 1 μg/mL for >40% of the dosing interval. However, when the target was set at 100% f T>MIC, only a 3-h infusion of 200 mg/kg/day q8h could achieve the target in this patient despite the presence of anuria. Conclusion: To optimise meropenem dosing in paediatric patients on ECMO and continuous haemodialysis, further study and PK monitoring are warranted.